Functional Aspects of Tapioca Farmers Problems During Sales in Tamilnadu (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this study, an effort was made to examine the problems encountered by tapioca farmers during the sales process. The research is based entirely on primary data collected through a structured interview schedule administered to farmers. The survey was carried out in Salem District, Tamil Nadu, with a sample of 500 tapioca farmers selected using a simple random sampling technique to ensure fair representation. A carefully designed interview instrument was employed to gather information on the challenges faced by farmers. To verify the reliability of the measurement scale, the data were subjected to item analysis, and the internal consistency was tested using Cronbach’s alpha coefficient. Subsequently, factor analysis and correlation analysis were applied to identify the functional dimensions and interrelationships among the problems reported by the farmers during sales.